2004
DOI: 10.1021/jp048260g
|View full text |Cite
|
Sign up to set email alerts
|

Surface Spectroscopy of Room-temperature Ionic Liquids on a Platinum Electrode:  A Sum Frequency Generation Study

Abstract: Sum frequency generation vibrational spectroscopy (SFG) and cyclic voltammetry (CV) measurements have been conducted on the ionic liquid/platinum electrode system. The room-temperature ionic liquid investigated is 1-butyl-3-methylimidazolium [BMIM]+ with [PF6]- or [BF4]- anions. SFG spectra are taken in situ under potential control from 2750 to 3300 cm-1 (C−H stretching region). Polarization-dependent SFG spectra are used to extract orientation information for the cation at the electrode surface. The SFG spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
181
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(202 citation statements)
references
References 49 publications
19
181
1
1
Order By: Relevance
“…Also for BMITf 2 N, we assume a flat orientation of the BMI + cation layer, which is generated and stabilized by π−π interactions and van-der-Waals forces between the alkyl chains. Sum-frequency-generation-spectroscopy (SFG) measurements of the interface between imidazolium-based ILs and polycrystalline platinum confirm this presumption of a flat lying imidazolium ring at negative potentials [44,45].…”
Section: Discussionmentioning
confidence: 84%
“…Also for BMITf 2 N, we assume a flat orientation of the BMI + cation layer, which is generated and stabilized by π−π interactions and van-der-Waals forces between the alkyl chains. Sum-frequency-generation-spectroscopy (SFG) measurements of the interface between imidazolium-based ILs and polycrystalline platinum confirm this presumption of a flat lying imidazolium ring at negative potentials [44,45].…”
Section: Discussionmentioning
confidence: 84%
“…A study using imidazolium bistriflamide, (F 3 CSO 2 ) 2 N − and BF 4 − salts suggested that a model of alternating anion and cation layers may be applicable to the data [29,30]. Baldelli [31,32] concluded that the double layer is one ion layer thick using sum frequency generation spectroscopy and electrochemistry to probe the electric field at the ionic liquid/electrode interface. The double layer capacitance in an ionic liquid is considerably smaller than in an aqueous solution and less than that predicted by having a perfect Helmholtz layer at the interface, which could result from the presence of ion pairs at the electrode surface at all potentials.…”
Section: Why Use Ionic Liquids For Electrodeposition?mentioning
confidence: 99%
“…A wide variety of experimental, theoretical, and simulation methods have been applied to the study of ILs at interfaces. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] Santos and Baldelli 112 have used interfacial sumfrequency generation ͑SFG͒ to show that at IL interfaces with gases or vacuum, alkyl chains on either the cations or the anions extend from the surface into the gas or vacuum. Rutherford backscattering spectra for the ͓bmim͔ + / ͓PF 6 ͔ − -vacuum interface also show the cation butyl group protruding from the bulk liquid into vacuum.…”
Section: Il Interfacesmentioning
confidence: 99%